Manajemen Risiko pada Rencana Pengamanan Air Minum (RPAM) Operator untuk Sumber Air Permukaan PDAM Krueng Peusangan Kabupaten Bireuen - Chakila (Jurnal Teknik Lingkungan, 2022)
Perusahaan Daerah Air Minum (PDAM) Krueng Peusangan uses water from Krueng Peusangan as its source of raw water. Krueng Peusangan water quality monitoring was carried out by BAPEDAL Aceh in 2016 and the first period was classified into "good condition" and in the second period classified into "lightly polluted". This incident indicates that the quality of Krueng Peusangan water is very fluctuating and can change at any time. This is a challenge for PDAM Krueng Peusangan in achieving the quality of water that can meet the quality standards based on Permenkes No.492 of 2010 tentang Persyaratan Kualitas Air Minum . Risk management is a tool that can control all the risks contained in raw water sources to consumers through a process of identification, assessment, risk prioritization, and recommendation of improvement plans that can be achieved through a Water Safety Plan (RPAM) or commonly known as Rencana Pengamanan Air Minum (RPAM) operator. From the identification process, PDAM Krueng Peusangan has 17 hazard events that could cause a decrease quality of water processed by Teupin Mane WTP, BRR WTP, and WKE WTP. In general, this is caused by activities upstream of the river, dosing of coagulants and disinfectants, leakage of distribution pipes, and water quality testing that are not routinely carried out for certain parameters. To deal with the hazard events identified, 41 control measures are required. After being reviewed, there were 22 improvement plans to deal with the major themes.In addition, operational monitoring are also provided with Standard Operating Procedure (SOP), Work Instruction (IK), internal dan external communications, supporting programs, reviews and audit.